Polyamide reverse osmosis membrane with high organic matter retention rate and pollution resistance as well as preparation method and application of polyamide reverse osmosis membrane
By introducing AAEM/polyvinylpyrrolidone copolymer on the crosslinked aromatic polyamide functional separation layer of the reverse osmosis membrane and forming chemical bonds, the problems of low TOC retention rate and poor anti-pollution performance are solved, and efficient organic retention and resistance are achieved Improved pollution performance and is suitable for a variety of industrial and household water treatment applications.
Patent Information
- Application Number
- CN202411485726.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing reverse osmosis membrane has a low retention rate of total organic carbon (TOC) and is susceptible to contamination during use, causing a decrease in flux, making it difficult to achieve efficient anti-pollution performance.
The crosslinked aromatic polyamide functional separation layer of the reverse osmosis membrane is introduced into the AAEM/polyvinylpyrrolidone copolymer on the surface and inside of the crosslinking layer, which improves the retention and anti-pollution performance through chemical bonding. The specific steps include interfacial polycondensation reaction and hot water cleaning to form crosslinks. The grafting amount of the copolymer is further enhanced by treatment with nitrite and sodium sulfite.
It significantly improves the retention rate and anti-pollution performance of the reverse osmosis membrane to TOC, maintains high throughput and high desalination rate, reduces the flux reduction rate after pollution, and restores the flux after cleaning. It is suitable for household water purification, Industrial pure water manufacturing and semiconductor industry.
Smart Images

Figure BDA0005098662230000041 
Figure BDA0005098662230000131 
Figure BDA0005098662230000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of reverse osmosis membrane preparation, and in particular relates to a polyamide reverse osmosis membrane with high organic matter interception rate and pollution resistance, and a preparation method and application thereof. Background Art
[0002] At present, the mainstream products of reverse osmosis membranes are three-layer composite membranes with polyester non-woven fabric as the base, polysulfone porous membrane as the middle support layer, and cross-linked aromatic polyamide ultra-thin layer as the surface actual functional separation layer. By adjusting the thickness and cross-linking degree of the cross-linked aromatic polyamide layer, reverse osmosis membranes with different fluxes and desalination rates can be obtained, thereby achieving different degrees of interception of water-soluble substances such as salt ions and macromolecular organic matter. Therefore, reverse osmosis membranes are often used in applications such as household tap water purification, industrial pure water production, industrial wastewater reuse and seawater desalination, which are mainly used for desalination.
[0003] However, in addition to areas where desalination is the main purpose, reverse osmosis membranes are also commonly used to filter total organic carbon (TOC) in pure water in industries such as semiconductors and display panels. When using pure water to clean silicon wafers or display panels, if the TOC residue in the water is too high, it will cause contamination of the silicon wafers or panels, thereby significantly increasing the product defect rate. For example, as a typical memory chip company scenario, the conductivity of the pure water to be treated is generally around 1 to 5 μS / cm, and the TOC concentration is in the range of 200 to 500 ppb; in order to improve the chip yield, it is necessary to use a reverse osmosis membrane to further filter the pure water, hoping that the conductivity of the produced water is less than 1 μS / cm, the TOC concentration is less than 50 ppb, and the larger the water output, the better.
[0004] Unlike salt ions with charge repulsion effect, the small molecular organic matter that constitutes TOC generally has no charge effect, which makes it impossible for the reverse osmosis membrane to use the charge repulsion effect of the carboxyl and amino groups inside the cross-linked aromatic polyamide to intercept TOC. It can only rely on the "pore size screening" effect of the angstrom-level pores inside the cross-linked polyamide. Therefore, the existing reverse osmosis membrane's interception rate for TOC is generally significantly lower than that of salt ions. In particular, it is more difficult to improve the TOC removal rate under the premise of maintaining the highest possible water permeability of the reverse osmosis membrane, and there are fewer related targeted studies.
[0005] In addition, whether the reverse osmosis membrane is used in the field of desalination or TOC removal, it will encounter the problem of membrane contamination and flux reduction during use. This is mainly because the cross-linked aromatic polyamide material is generally hydrophilic, and some highly hydrophobic organic pollutants such as proteins, surfactants, emulsified hydrocarbons, and microorganisms are easily adsorbed on the membrane surface through hydrophobic intermolecular interactions and are difficult to clean. This requires frequent acid and alkali cleaning of the reverse osmosis membrane during operation.
[0006] In order to improve the anti-pollution performance of reverse osmosis membranes, there are currently many literature and patent studies, mainly focusing on improving the hydrophilicity of the reverse osmosis membrane surface, reducing the roughness of the membrane surface, and making the membrane surface approach electrical neutrality. Despite so many studies on anti-pollution coatings for reverse osmosis membranes, considering the acid and alkali resistance and oxidation resistance of the coating materials, the main method reported in patents with industrial value is to introduce hydrophilic polymers on the surface of the reverse osmosis membrane, such as polyvinyl alcohol (such as patent document CN102921315A, patent document CN105008031A, patent document CN105008031A), polyethylene glycol (such as patent document CN102363113A, patent document CN1180876C), polyoxazoline (such as patent document CN101605592A), polyacrylic acid (such as patent document CN111787997A, patent document CN105611994A, patent document CN110536743A), etc.
[0007] In the industrialized anti-fouling reverse osmosis membrane, polyethylene glycol and polyoxazoline have been introduced into the surface of the reverse osmosis membrane due to their reactive active groups, and show good anti-fouling performance. Although polyvinyl pyrrolidone (PVP) has excellent anti-fouling performance, it cannot directly form chemical bonds with the amino and carboxyl groups of the aromatic polyamide cross-linked with the surface of the reverse osmosis membrane due to the lack of reactive active groups in its polymer side chains. The existing research is to introduce it into the surface of the reverse osmosis membrane through the strong hydrogen bonding formed by the tannic acid intermediate layer containing polyphenols (Wu J, Wang Z, Yan W, et al. Improving the hydrophilicity and fouling resistance of RO membranes by surface immobilization of PVP based on a metal-polyphenol precursor layer [J]. Journal of Membrane Science, 2015, 496: 58-69. DOI: 10.1016 / j.memsci.2015.08.044.). However, since polyvinyl pyrrolidone has no chemical bond to the membrane surface, simple acid-base cleaning can easily destroy the hydrogen bonds and cause coating loss, making it of no commercial significance.
[0008] Therefore, developing a polyamide reverse osmosis membrane with high organic matter retention and anti-fouling is of great significance for improving the retention effect of the reverse osmosis membrane and reducing the operating cost of the reverse osmosis membrane. Summary of the invention
[0009] The purpose of the present invention is to provide a polyamide reverse osmosis membrane with high organic matter retention rate and anti-pollution and its preparation method and application, in view of the problems existing in the prior art in improving the anti-pollution and TOC retention of reverse osmosis membranes, and to graft AAEM / polyvinyl pyrrolidone copolymer to the surface and interior of the cross-linked aromatic polyamide functional separation layer of the reverse osmosis membrane, so as to effectively improve the organic matter retention performance and anti-pollution performance of the reverse osmosis membrane while maintaining high flux and high desalination rate.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] In the first aspect, a polyamide reverse osmosis membrane with high organic matter rejection rate and anti-pollution is provided, which comprises: a base layer, a porous support layer and a functional separation layer in sequence; the functional separation layer comprises: a cross-linked polyamide and an AAEM / NVP copolymer, and the cross-linked polyamide and the AAEM / NVP copolymer in the functional separation layer are connected by chemical bonds.
[0012] According to the polyamide reverse osmosis membrane provided by the invention, in some embodiments, in the functional separation layer, the AAEM / NVP copolymer is connected through a chemical bond formed between the acetoacetyl group of its side chain and the terminal amino group of the cross-linked polyamide and / or is connected to the diazonium salt obtained after diazotization of the terminal amino group through a chemical bond formed.
[0013] In the present invention, the functional separation layer comprises a chemical bond formed between the acetoacetyl group and the terminal amino group of the cross-linked polyamide, an azo group and a phenolic hydroxyl group. The azo group is derived from a chemical group formed by the reaction of the diazonium salt and the acetoacetyl group of the copolymer. Figure 3 As shown in the figure, the azo group in the functional separation layer can further increase the cross-linking degree of the cross-linked polyamide desalination layer and improve the interception rate of small molecule organic matter TOC; the phenolic hydroxyl group is derived from the chemical group formed by the hydrolysis of the unreacted diazonium salt at high temperature, see the attached manual for details. Figure 4 As shown, the phenolic hydroxyl groups in the functional separation layer can, on the one hand, increase the hydrophilicity inside the polyamide desalination layer and improve the permeation flux; on the other hand, they can utilize the hydrogen bonding between the phenolic hydroxyl groups and between the phenolic hydroxyl groups and the amide bonds to avoid loss of desalination rate.
[0014] According to the polyamide reverse osmosis membrane provided by the invention, in some embodiments, the AAEM / NVP copolymer is a product obtained by free radical polymerization of acetoacetoxyethyl methacrylate (AAEM) and N-vinyl pyrrolidone (NVP) as monomers.
[0015] In some embodiments, the side chain of the AAEM / NVP copolymer contains a reactive acetoacetyl group and a hydrophilic pyrrolidone group, and its chemical structure is shown in formula (I):
[0016]
[0017] wherein x and y are positive integers (e.g., independently selected from 10, 12, 13, 15, 17, 18, 19, 20, 25, 30, 36, 40, 45, 50, 55, 60, 65, 70, 75, 80, 86, 90, 95, 100, 500, etc.), and the value range satisfying the relationship x / (x+y) is 0.05 to 0.3; for example, x / (x+y) is 0.055, 0.06, 0.07, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.24, 0.25, 0.26, 0.28.
[0018] Herein, the method for obtaining the AAEM / NVP copolymer can refer to the free radical copolymerization technology known in the art, which will not be described in detail here. There is no particular limitation on the solvent used for free radical copolymerization, as long as it can dissolve AAEM and NVP, such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dioxane, etc.; considering the solubility of the AAEM / NVP copolymer in the solvent, N-methylpyrrolidone is preferred. There is no particular limitation on the initiator used for free radical copolymerization, which can be selected from redox initiators, azo initiators, etc., as long as free radicals can be generated. Considering the solvent compatibility and polymerization reaction temperature, azo initiators are preferred, such as azobisisobutyronitrile initiator. Regarding the solid content of the finally synthesized copolymer in the solvent, it can be in the range of 5% to 60%, preferably in the range of 10% to 50%, and further preferably in the range of 30% to 45%. In the present invention, after the free radical polymerization reaction of AAEM and NVP in a solvent is completed, the obtained copolymer does not need to be separated or purified and can be used directly.
[0019] In some embodiments, the weight average molecular weight of the AAEM / NVP copolymer is greater than or equal to 5,000 and less than or equal to 1000,000, preferably greater than or equal to 10,000 and less than or equal to 800,000, and more preferably greater than or equal to 50,000 and less than or equal to 500,000. The weight average molecular weight of the AAEM / NVP copolymer can be, for example, 5,500, 5,800, 6,000, 6,500, 7,000, 7,500, 8,000, 9,000, 10,000, 11,000, 12,000, 15,000, 18,000, 20,000, 30,000, 40,000, 50,000, 60,000, 80,000, 100,000, 120,000, 150,000, 200,000, 300,000, 550,000, 600,000, 850,000, or 900,000.
[0020] In some embodiments, the cross-linked polyamide is obtained by interfacial polycondensation reaction of an aqueous solution containing m-phenylenediamine and triethyl phosphate with an oil solution containing trimesoyl chloride on the surface of the porous support layer. Herein, the aromatic cross-linked polyamide layer can be a common functional layer of a reverse osmosis membrane in the prior art, and its relevant preparation process can refer to the prior art, which is not described in detail here.
[0021] In some embodiments, the base layer is selected from one or more of polyester nonwoven fabric, polyethylene porous film and polypropylene porous film.
[0022] In some embodiments, the porous support layer is selected from one or more of a polysulfone porous support layer, a polyethersulfone porous support layer, and a polyacrylonitrile porous support layer.
[0023] The method for combining the base layer and the porous support layer is well known to those skilled in the art and will not be described in detail here.
[0024] In some embodiments, the static contact angle of the functional separation layer in the polyamide reverse osmosis membrane is greater than or equal to 20° and less than or equal to 40°; for example, the static contact angle is 22°, 24°, 25°, 28°, 30°, 32°, 34°, 35°, 36°, or 38°.
[0025] The static contact angle test can be understood, for example, as follows: after the polyamide reverse osmosis membrane is placed in a hot air oven at 80°C for 24 hours, 2 microliters of deionized water is dropped onto the surface of the functional separation layer of the reverse osmosis membrane for a static contact angle test, which is the contact angle 10 seconds after the pure water is dropped onto the surface of the functional separation layer.
[0026] In some embodiments, at pH = 6.5, the surface Zeta potential of the functional separation layer is -35 mV to -10 mV, for example, the surface Zeta potential is -32 mV, -30 mV, -28 mV, -25 mV, -22 mV, -20 mV, -18 mV, -15 mV, -12 mV.
[0027] In some embodiments, the polyamide reverse osmosis membrane has a salt rejection rate (Rs) of 99.6% and above (e.g., 99.7%, 99.75%, 99.8%, 99.85%, 99.9%, 99.92%, 99.95%), a TOC removal rate (Rt) of 85% and above (e.g., 86%, 87%, 88%, 89%, 90%, 92%, 94%, 95%), and a permeate flux of 60 L / (m 2 ·h) and above (for example, 62L / (m 2 ·h)、65L / (m 2 ·h)、68L / (m 2 ·h)、70L / (m 2 ·h)、72L / (m 2 ·h)、75L / (m 2 h)).
[0028] For example, after filtering an aqueous solution at 25°C, pH 7.0, sodium chloride concentration of 1500-2000 mg / L, and isopropanol concentration of 100 mg / L for 1 hour under a pressure of 1.03 MPa, the polyamide reverse osmosis membrane has a sodium chloride retention rate of 99.6% or more, an isopropanol retention rate of 85% or more, and a permeate flux of 60 L / (m 2 h) and above.
[0029] In some embodiments, the flux decline rate of the polyamide reverse osmosis membrane after contamination is greater than or equal to 5% and less than or equal to 25% (for example, 6%, 7%, 8%, 10%, 12%, 15%, 16%, 18%, 20%, 22%, 24%); the flux recovery rate after cleaning is greater than or equal to 98% and less than or equal to 100% (for example, 98.2%, 98.5%, 98.8%, 99%, 99.2%, 99.4%, 99.5%, 99.6%, 99.8%, 99.9%).
[0030] In a second aspect, a method for preparing the polyamide reverse osmosis membrane as described above is provided, comprising the following steps:
[0031] S1, subjecting an aqueous solution containing m-phenylenediamine and triethyl phosphate to an interfacial polycondensation reaction with an oil solution containing trimesoyl chloride on the surface of a porous support layer to form a cross-linked aromatic polyamide-I, thereby obtaining a primary reverse osmosis membrane;
[0032] S2, contacting the primary reverse osmosis membrane obtained in step S1 with the post-crosslinking aqueous solution to react, and then washing in hot water to form a cross-linked aromatic polyamide-II, thereby obtaining a secondary reverse osmosis membrane;
[0033] Preferably, the post-crosslinking aqueous solution contains m-phenylenediamine and alcohol additives;
[0034] Preferably, the alcohol additive is selected from any one of methanol, ethanol, isopropanol, ethylene glycol, and glycerol;
[0035] There is no particular limitation on the secondary crosslinking reaction of the crosslinked aromatic polyamide with the metaphenylenediamine in the post-crosslinking aqueous solution, as long as the residual acyl chloride groups on the surface of the crosslinked aromatic polyamide can further react with the amino groups of the metaphenylenediamine;
[0036] The post-crosslinking aqueous solution is used to contact the cross-linked aromatic polyamide surface formed by interfacial polycondensation, which not only enables the unreacted acyl chloride groups remaining on the surface to continue to react with the amino groups, reducing the proportion of carboxyl-terminated linear polyamide on the surface and inside of the cross-linked aromatic polyamide, initially reducing the size of the angstrom-level "pores", but also increases the terminal amino group content on the surface of the cross-linked polyamide;
[0037] S3, contacting the secondary reverse osmosis membrane obtained in step S2 with an aqueous solution containing AAEM / NVP copolymer to react, and then washing in hot water to form a cross-linked aromatic polyamide-III, thereby obtaining a tertiary reverse osmosis membrane;
[0038] By utilizing the chemical bond formed between the acetoacetyl group of the AAEM / NVP copolymer and the amino group on the surface of the cross-linked aromatic polyamide, the amino groups on the surface of the membrane are further cross-linked, thereby increasing the degree of cross-linking and further reducing the size of the angstrom-level "pores" in the cross-linked aromatic polyamide. In addition, since the oil phase solvent containing trimesoyl chloride still remains inside the cross-linked aromatic polyamide, the pyrrolidone ring of the AAEM / NVP copolymer has a certain surface activity, making it easier for the AAEM / NVP copolymer to enter the loose structure inside the cross-linked aromatic polyamide.
[0039] S4, the three-stage reverse osmosis membrane obtained in step S3 is first immersed in a nitrous acid aqueous solution for reaction, then immersed in an aqueous solution containing sodium sulfite and AAEM / NVP copolymer for reaction, and then washed with hot water to obtain the polyamide reverse osmosis membrane.
[0040] Some of the terminal amino groups that remain after the reaction of the cross-linked aromatic polyamide and the AAEM / NVP copolymer react with nitrous acid to form diazonium salts, which can then continue to react with the acetoacetyl groups of the AAEM / NVP copolymer, thereby further increasing the surface grafting amount of the AAEM / NVP copolymer and once again reducing the size of the angstrom-level "pores" in the cross-linked aromatic polyamide.
[0041] In the present invention, the polyamide reverse osmosis membrane with high organic matter retention and anti-pollution can have the aforementioned performance characteristics as long as it has a functional separation layer with the above-mentioned structural characteristics (for example, the static contact angle of the functional separation layer in the polyamide reverse osmosis membrane is greater than or equal to 20° and less than or equal to 40°; and / or, the surface Zeta potential value of the functional separation layer at pH=6.5 is -35mV to -10mV; and / or, the salt rejection rate (Rs) of the polyamide reverse osmosis membrane is 99.6% or more, the TOC removal rate (Rt) is 85% or more, and the permeate flux is 60L / (m 2 ·h) and above; the flux decrease rate of the polyamide reverse osmosis membrane after contamination is greater than or equal to 5% and less than or equal to 25%, and the flux recovery rate after cleaning is greater than or equal to 98% and less than or equal to 100%), which is not limited to the specific preparation method.
[0042] In the preparation method of the present invention, the numbers "I", "II", "III" and "primary", "secondary", "tertiary" and the like have no specific meanings and are only used to indicate the operation process between the steps.
[0043] According to the preparation method provided by the present invention, in step S1:
[0044] Regarding the aqueous phase solution containing m-phenylenediamine and triethyl phosphate, in terms of mass percentage, the mass concentration of m-phenylenediamine can be in the range of 0.5% to 10%, preferably in the range of 1% to 7%; the mass concentration of triethyl phosphate can be in the range of 0.05% to 1%, preferably in the range of 0.1% to 0.8%, and further preferably in the range of 0.2% to 0.5%. In order to obtain a cross-linked aromatic polyamide desalination layer with higher flux and desalination rate, the mass concentration ratio of m-phenylenediamine to triethyl phosphate in the aqueous phase solution can be in the range of 20:1 to 5:1, preferably in the range of 20:1 to 8:1, and further preferably in the range of 15:1 to 8:1.
[0045] The temperature of the aqueous phase solution may be 0 to 100°C, preferably 5 to 60°C, and more preferably 20 to 45°C.
[0046] Regarding the method of contacting the aqueous solution containing m-phenylenediamine and triethyl phosphate with the surface of the porous support layer, as long as the aqueous solution can be evenly contacted with the surface of the base membrane, the aqueous solution can be evenly coated on the surface of the base membrane by coating, or the base membrane can be directly immersed in the aqueous solution.
[0047] The contact time between the aqueous solution and the basement membrane can be between 5 seconds and 10 minutes, preferably between 10 seconds and 2 minutes. Next, it is necessary to remove the excess aqueous solution on the surface of the basement membrane. The removal method is not limited in any way, as long as the aqueous solution can be evenly infiltrated on the surface of the basement membrane and there are no water droplets visible to the naked eye on the surface of the basement membrane. The basement membrane can be vertically placed to allow the aqueous solution to flow down naturally and then dry naturally, or an extrusion roller or air knife can be directly used to first remove most of the excess aqueous solution, and then the remaining aqueous solution can be removed by natural drying or oven drying. Next, the oil phase solution containing trimesoyl chloride is evenly coated on the surface of the basement membrane, and static contact occurs on it to cause an interfacial polycondensation reaction to form a cross-linked aromatic polyamide desalting layer.
[0048] Regarding the interfacial polycondensation reaction of m-phenylenediamine and trimesoyl chloride, it not only occurs in the pores of the porous support layer, but also occurs in the non-porous areas on the surface of the porous support layer. The finally formed cross-linked aromatic polyamide desalination layer is combined with the porous support layer in a "physical interlocking" manner.
[0049] The temperature of the static interfacial polycondensation reaction is mainly determined by the temperature of the oil phase solution, and can be 10 to 40°C, preferably 15 to 35°C, and more preferably 20 to 30°C. The static contact interfacial polycondensation reaction time can be 0.5 seconds to 5 minutes, preferably 5 seconds to 2 minutes, and more preferably 10 seconds to 1 minute. When the static contact interfacial polycondensation reaction time is less than 0.5 seconds, the interfacial polycondensation reaction is insufficient and a complete polyamide desalination layer cannot be formed; when the static contact interfacial polycondensation reaction time is more than 5 minutes, the formed polyamide desalination layer is too thick, the membrane permeation flux is too low, and the production efficiency is reduced.
[0050] The concentration of trimesoyl chloride in the oil phase solution can be in the range of 0.05% to 1%, preferably in the range of 0.08% to 0.5%, and more preferably in the range of 0.1% to 0.3%, by mass percentage. In order to form a cross-linked aromatic polyamide desalination layer with higher flux and desalination rate, the ratio between the concentration of mesophenylenediamine in the aqueous phase solution and the concentration of trimesoyl chloride in the oil phase solution can be limited, for example, 30:1 to 5:1, preferably 15:1 to 5:1, and more preferably 15:1 to 10:1.
[0051] Next, it is necessary to remove the excess oil phase solution from the membrane surface. There is no limitation on the method for removing the oil phase solution, as long as the polyamide desalting layer is not damaged. For example, the oil phase solvent can be volatilized by directly using an oven, or the membrane can be vertically placed to allow the oil phase solution to flow down naturally and then dry naturally, or the solvent can be directly removed by physical methods such as guide rollers, air knives, and water knives.
[0052] According to the preparation method provided by the present invention, in step S2:
[0053] The concentration of m-phenylenediamine contained in the post-crosslinking aqueous solution can be in the range of 0.001% to 1% by mass, preferably in the range of 0.005% to 0.5%, and more preferably in the range of 0.01% to 0.1%. In order to promote the diffusion of m-phenylenediamine into the crosslinked aromatic polyamide, an alcohol additive can be added thereto. As the alcohol additive, it can be selected from methanol, ethanol, isopropanol, ethylene glycol, glycerol, etc.; the concentration of the alcohol additive contained in the post-crosslinking aqueous solution can be in the range of 1% to 20% by mass, preferably in the range of 5% to 10%. The temperature of the post-crosslinking aqueous solution containing m-phenylenediamine can be 0°C to 100°C, preferably 20°C to 90°C, and more preferably 60°C to 85°C.
[0054] Regarding the method of contacting the post-crosslinked aqueous solution containing meta-phenylenediamine with the cross-linked aromatic polyamide, it is sufficient as long as the aqueous solution can be brought into uniform contact with the surface of the cross-linked aromatic polyamide. For example, the aqueous phase solution can be uniformly coated on the membrane surface by coating, or the reverse osmosis membrane can be directly immersed in the aqueous phase solution.
[0055] The contact time of the post-crosslinking aqueous solution and the crosslinked aromatic polyamide may be, for example, 5 seconds to 10 minutes, preferably 10 to 2 minutes. The contact temperature of the post-crosslinking aqueous solution and the crosslinked aromatic polyamide is mainly determined by the temperature of the post-crosslinking aqueous solution, for example, 45°C to 100°C, preferably 60°C to 95°C, and more preferably 75°C to 90°C.
[0056] Regarding the hot water cleaning method, for example, the reverse osmosis membrane can be directly immersed in hot water. Regarding the temperature of the hot water, for example, it can be 45° C. to 100° C., preferably 60° C. to 95° C., and more preferably 75° C. to 90° C. Regarding the immersion time, for example, it can be 5 seconds to 10 minutes, preferably 10 seconds to 2 minutes, and more preferably 30 to 1 minute.
[0057] According to the preparation method provided by the present invention, in step S3:
[0058] Regarding the reaction formula of its specific reaction, such as Figure 1 As shown;
[0059] The concentration of the aqueous solution containing the AAEM / NVP copolymer can be, for example, in the range of 0.001% to 1%, preferably in the range of 0.01% to 0.5%, and more preferably in the range of 0.01% to 0.1%, in terms of mass percentage. The contact temperature of the aqueous solution containing the AAEM / NVP copolymer and the cross-linked aromatic polyamide is mainly determined by the temperature of the aqueous solution containing the AAEM / NVP copolymer, and can be, for example, 45° C. to 100° C., preferably 60° C. to 95° C., and more preferably 75° C. to 90° C. The contact time of the aqueous solution containing the AAEM / NVP copolymer and the cross-linked aromatic polyamide can be, for example, 5 seconds to 10 minutes, preferably 10 seconds to 2 minutes, and more preferably 30 seconds to 1 minute.
[0060] Regarding the method of washing in hot water, for example, the reverse osmosis membrane can be directly immersed in hot water. Regarding the temperature of the hot water, for example, it can be 45° C. to 100° C., preferably 60° C. to 95° C., and more preferably 75° C. to 90° C. Regarding the time of immersion in hot water, for example, it can be 5 seconds to 10 minutes, preferably 10 seconds to 2 minutes, and more preferably 30 seconds to 1 minute.
[0061] According to the preparation method provided by the present invention, in step S4:
[0062] Regarding the reaction formula of cross-linked aromatic polyamide reacting with nitrous acid to form diazonium salt, such as Figure 2 shown.
[0063] Regarding the nitrous acid aqueous solution, for example, the pH value of the sodium nitrite aqueous solution can be adjusted to be acidic by hydrochloric acid to form a nitrous acid aqueous solution; sodium nitrite reacts with hydrochloric acid to form nitrous acid, and the nitrous acid reacts with the terminal amino group to convert the terminal amino group into a diazonium salt.
[0064] Regarding the concentration of the aqueous nitrous acid solution, in terms of mass percentage, it can be, for example, in the range of 0.05% to 1%, preferably in the range of 0.1% to 0.5%, and further preferably in the range of 0.2% to 0.4%; regarding the pH value of the aqueous nitrous acid solution, it can be, for example, in the range of 1 to 5, preferably in the range of 2 to 4, and further preferably in the range of 2 to 3.
[0065] The immersion time of the reverse osmosis membrane in the aqueous nitrous acid solution may be, for example, 5 seconds to 24 hours, preferably 10 seconds to 2 hours, and more preferably 10 seconds to 60 seconds.
[0066] Next, the reverse osmosis membrane is immersed in an aqueous solution containing sodium sulfite and AAEM / NVP copolymer; the reaction formula of AAEM / NVP copolymer and diazonium salt is as follows: Figure 3 shown.
[0067] In the aqueous solution containing the AAEM / NVP copolymer and sodium sulfite, the concentration of sodium sulfite, by mass percentage, for example, can be in the range of 0.1% to 10%, preferably in the range of 0.2% to 5%, and further preferably in the range of 0.5% to 2%; the concentration of the AAEM / NVP copolymer, by mass percentage, for example, can be in the range of 0.001% to 1%, preferably in the range of 0.01% to 0.5%, and further preferably in the range of 0.01% to 0.1%.
[0068] The immersion time of the reverse osmosis membrane in the aqueous solution containing the AAEM / NVP copolymer and sodium sulfite may be, for example, 5 seconds to 24 hours, preferably 10 seconds to 1 hour, and more preferably 10 seconds to 60 seconds.
[0069] In order to better promote the reaction between the AAEM / NVP copolymer and the diazonium salt in the cross-linked aromatic polyamide, the concentration ratio and temperature of the sodium sulfite and the AAEM / NVP copolymer can be limited. The concentration ratio of the sodium sulfite and the AAEM / NVP copolymer can be, for example, 200:1 to 10:1, preferably 150:1 to 50:1, and more preferably 100:1 to 50:1.
[0070] Finally, the reverse osmosis membrane is washed with hot water to obtain the final reverse osmosis membrane; in this operation, the unreacted diazonium salt remaining in the cross-linked aromatic polyamide is hydrolyzed to phenolic hydroxyl groups, and the reaction formula is as follows: Figure 4 As shown;
[0071] Regarding the method of hot water cleaning, for example, the reverse osmosis membrane can be directly immersed in hot water; regarding the temperature of the hot water, for example, it can be 45°C to 100°C, preferably 60°C to 95°C, and more preferably 75°C to 90°C; regarding the immersion time in hot water, for example, it can be 5 seconds to 10 minutes, preferably 10 seconds to 2 minutes, and more preferably 30 seconds to 1 minute.
[0072] In this article, the methods for forming chemical bonds between the AAEM / NVP copolymer and the cross-linked aromatic polyamide include: utilizing the reaction of the acetoacetyl active groups in the AAEM / NVP copolymer with the terminal amino groups remaining before the nitrous acid treatment, and utilizing the reaction of the acetoacetyl active groups in the AAEM / NVP copolymer with the diazonium salt after the nitrous acid treatment.
[0073] In the present invention, on the one hand, through the further cross-linking effect of the acetoacetyl group in the AAEM / NVP copolymer on the cross-linked aromatic polyamide, the cross-linking reaction of the m-phenylenediamine and the residual acyl chloride group of the polyamide together plays a role in reducing the angstrom-level "pores" of the functional separation layer, and the formed diazonium salt can continue to react with the acetoacetyl group of the AAEM / NVP copolymer, thereby further increasing the surface grafting amount of the AAEM / NVP copolymer, once again reducing the size of the angstrom-level "pores" in the cross-linked aromatic polyamide, thereby improving the interception effect on uncharged organic matter and maintaining a high desalination rate; on the other hand, the copolymer embedded in the cross-linked aromatic polyamide promotes the transfer of water molecules due to the hydrophilicity of the pyrrolidone ring, which not only compensates for the increase in water permeability resistance caused by the introduction of the surface copolymer and avoids the loss of flux, but also the copolymer on the membrane surface forms a PVP "polymer brush" with a strong chemical bond connection on the surface of the cross-linked polyamide, which reduces the adhesion of pollutants on the membrane surface and improves the anti-pollution property of the membrane.
[0074] In a third aspect, there is provided a polyamide reverse osmosis membrane as described above or a polyamide reverse osmosis membrane prepared by the preparation method as described above, and its use in the field of desalination.
[0075] According to the application provided by the present invention, in some embodiments, the polyamide reverse osmosis membrane is used in the fields of household water purification, industrial pure water production, industrial wastewater treatment, and organic matter removal in pure water for the semiconductor industry. Herein, the specific application steps and operating conditions of the polyamide reverse osmosis membrane can be conventional operations in the field and will not be repeated here.
[0076] Acetoacetoxyethyl methacrylate (AAEM) is a methacrylic acid monomer containing two active groups, one is a terminal double bond and the other is a terminal acetoacetyl group. Among them, the terminal double bond allows AAEM to copolymerize with various monomers such as N-vinyl pyrrolidone (NVP) to form a copolymer; the terminal acetoacetyl group, due to the conjugation effect of the dicarbonyl group, makes the hydrogen (-H) on the middle methylene group extremely active, and is easy to react with various groups such as amino groups, aldehyde groups, diazonium salts, etc. to form a strong chemical bond. The present invention utilizes the reactivity of the acetoacetyl group in AAEM and the good hydrophilicity and anti-protein adhesion properties of the NVP copolymer, and forms an AAEM / polyvinyl pyrrolidone copolymer containing acetoacetyl active groups by free radical polymerization of AAEM and NVP, and grafts it to the surface and inside of the cross-linked aromatic polyamide functional separation layer of the reverse osmosis membrane, which effectively improves the organic matter retention performance and anti-pollution performance of the reverse osmosis membrane while maintaining high flux. The introduction of AAEM / NVP copolymer into the polyamide desalination layer not only significantly improves the organic matter retention performance and anti-pollution performance without losing the permeation flux, but also maintains a high desalination rate.
[0077] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0078] The polyamide reverse osmosis membrane provided by the present invention improves its organic matter retention and anti-pollution performance while maintaining high reverse osmosis membrane flux and desalination rate; in addition, the technical solution of the present invention is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 A schematic diagram of the reaction between the AAEM / NVP copolymer and the terminal amino group of the cross-linked aromatic polyamide is shown;
[0080] Figure 2 A schematic diagram of the reaction formula for the reaction of the residual terminal amino group in the cross-linked aromatic polyamide with nitrous acid to form a diazonium salt is shown;
[0081] Figure 3 The schematic diagram of the reaction between the AAEM / NVP copolymer and the diazonium salt formed by the cross-linked aromatic polyamide is shown;
[0082] Figure 4 The schematic diagram of the reaction formula for the formation of phenolic hydroxyl groups after the unreacted diazonium salt remaining in the cross-linked aromatic polyamide is hydrolyzed. DETAILED DESCRIPTION
[0083] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.
[0084] Unless otherwise specified, the raw materials used in the following examples or comparative examples are all commercially available conventional raw materials; the main raw material information is shown in Table 1 below:
[0085] Table 1
[0086]
[0087]
[0088] The synthesis method of the AAEM / NVP copolymer used in each embodiment of the present invention comprises the following steps:
[0089] (1) Preparation of primer and preheating of initiator: 210 g of N-methylpyrrolidone was weighed into a 1 L four-necked round-bottom flask, placed in a water bath, and the stirrer speed was set to 100-150 rpm. The nitrogen main valve and the sub-valve were opened at the same time to ensure that nitrogen was emitted steadily; 40 g of N-methylpyrrolidone and 0.96 g of azobisisobutyronitrile were weighed, shaken until completely dissolved, and then added into the four-necked round-bottom flask, and the temperature was raised to 78° C.;
[0090] (2) Preparation of drop solution and drop reaction: 60 g of N-methylpyrrolidone, 240 g of AAEM and NVP in total were weighed and mixed with 1.44 g of azobisisobutyronitrile to prepare a drop solution, and the drop solution was shaken evenly;
[0091] Begin to uniformly add the prepared dropwise solution into the four-necked round-bottom flask, maintain the reaction temperature at 78±1° C., and add for about 2 hours; wherein the ratio x / (x+y) of the molar amount of AAEM to the total molar amount of the monomers (AAEM and NVP) is adjusted according to different embodiments;
[0092] (3) Preparation of post-treatment solution and post-treatment: 26 g of N-methylpyrrolidone and 1.2 g of azobisisobutyronitrile were weighed and mixed to prepare a post-treatment solution, which was shaken until completely dissolved. The solution was then added to the four-necked round-bottom flask and the system was controlled to react at 80±1° C. for 2 h. Finally, the nitrogen flow was stopped and the system temperature was allowed to drop to room temperature to obtain an AAEM / NVP copolymer with a solid content of 40%.
[0093] Structural Characterization and Test Methods
[0094] The structural characterization and testing methods of the reverse osmosis membranes obtained in each embodiment or comparative example are described as follows:
[0095] (1) Contact angle
[0096] After the reverse osmosis membrane to be tested is soaked in pure water for 12 hours, it is placed in a 60℃ oven for drying for 24 hours. Then, in an environment of temperature 25±2℃ and humidity 40%-60%, 2 microliters of deionized water is dropped onto the surface of the functional separation layer of the reverse osmosis membrane using the OCA25 video optical contact angle meter produced by Dataphysics to perform a static contact angle test. The contact angle is taken 10 seconds after the pure water is dropped onto the surface of the functional separation layer.
[0097] (2) Zeta potential
[0098] The reverse osmosis membrane to be tested was soaked in pure water for 12 hours, and then dried in a 60°C oven for 24 hours. Then, the Zeta potential at pH = 6.5 was tested using a SurPASS solid surface Zeta potential tester produced by Anton Paar, with 1 mM potassium chloride solution as the mobile phase and a flow channel gap of 100±5 μm.
[0099] (3) Salt rejection rate (Rs), TOC removal rate (Rt) and permeation flux
[0100] Salt rejection rate and permeation flux are two important parameters for evaluating the separation performance of reverse osmosis membranes. The present invention evaluates the separation performance of reverse osmosis membranes according to the contents of GB / T32373-2005 "Test Method for Reverse Osmosis Membrane".
[0101] The salt rejection rate (Rs) is defined as: under certain operating conditions, the difference between the reverse osmosis membrane feed solution salt concentration (Cf, s) and the permeate salt concentration (Cp, s), divided by the feed solution salt concentration (Cf, s). The calculation formula is as follows:
[0102]
[0103] TOC removal rate (Rt) is defined as: under certain operating conditions, the difference between the reverse osmosis membrane feed isopropanol concentration (Cf, t) and the permeate isopropanol concentration (Cp, t) obtained by gas chromatography test, divided by the feed liquid salt concentration (Cf, t). The calculation formula is as follows:
[0104]
[0105] The definition of permeation flux is: the volume of water that passes through a unit membrane area per unit time under certain operating conditions, and its unit is L / (m 2 h);
[0106] The reverse osmosis membrane performance test conditions are as follows: the feed liquid is 2000 mg / L sodium chloride and 100 mg / L isopropanol aqueous solution, the temperature is 25°C, the solution pH is 7.0, the operating pressure is 1.55 MPa, and it runs continuously for 60 minutes.
[0107] (4) Anti-pollution performance
[0108] Triton X-100 was used as a model pollutant, and the flux decrease rate after pollution and the flux recovery rate after cleaning were used to characterize the anti-fouling performance of reverse osmosis.
[0109] Flux decline rate after pollution = (F1-F2) / F1;
[0110] Flux recovery rate after cleaning = F3 / F1;
[0111] in:
[0112] F1 is the flux of the permeable membrane to be tested after filtering an aqueous solution at 25°C, pH 7.0, and sodium chloride concentration of 2000 mg / L at a pressure of 1.03 MPa for 1 hour;
[0113] F2 is the flux after adding Triton X-100 to the aforementioned sodium chloride aqueous solution to a concentration of 100 mg / L and continuing to run for 48 hours;
[0114] F3 is the flux after the membrane is first cleaned in a sodium hydroxide solution at 35°C and pH 12.0 for 1 hour, then cleaned in a hydrochloric acid solution at 25°C and pH 2.0 for 1 hour, and finally filtered at a pressure of 1.03 MPa against an aqueous solution at 25°C, pH 7.0 and a sodium chloride concentration of 2000 mg / L for 1 hour.
[0115] Comparative Example 1:
[0116] The reverse osmosis membrane is prepared using a pilot production line, and the steps are as follows:
[0117] S1. At 25° C., a dimethylformamide solution containing 16.5 wt% polysulfone is uniformly coated on a polyester non-woven fabric substrate, the thickness of the wet coating is 150 μm, and after staying in the air for 1.5 seconds, it is immersed in deionized water at 15° C. for 1 minute, and then immersed in deionized water at 70° C. for 2 minutes to obtain a base membrane containing a non-woven fabric substrate and a polysulfone porous support layer;
[0118] The base film obtained as above is immersed in an aqueous solution containing m-phenylenediamine (content of 2.0wt%) and triethyl phosphate (content of 0.2wt%) for 30 seconds, and then the base film is lifted up in the vertical direction and pulled out of the aqueous solution tank, and then the excess aqueous solution on the surface is removed by using a rubber squeeze roller; then, an n-decane oil solution containing trimesoyl chloride (content of 0.11wt%) is evenly coated on the surface of the base film, and after standing for reaction for 30 seconds, the excess oil solution on the surface is removed to obtain a primary reverse osmosis membrane including a non-woven fabric substrate, a porous support layer and a polyamide desalination layer;
[0119] S2. Wash the primary reverse osmosis membrane obtained above in hot water at 80°C for 3 minutes.
[0120] S3, then immersed in a sodium nitrite aqueous solution with a pH of 3.0 and a solute content of 0.3wt% (pH adjusted with hydrochloric acid) for 1 minute, then immersed in a sodium sulfite reducing aqueous solution at 60°C and a solute content of 1wt% for 1 minute, and finally washed in hot water at 90°C for 2 minutes to obtain the final reverse osmosis membrane.
[0121] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling properties. The test results are recorded in Tables 2 and 3, respectively.
[0122] Comparative Example 2
[0123] The reverse osmosis membrane is prepared using a pilot production line, and the steps are as follows:
[0124] S1. At 25° C., a dimethylformamide solution containing 16.5 wt% polysulfone is uniformly coated on a polyester non-woven fabric substrate, the thickness of the wet coating is 150 μm, and after staying in the air for 1.5 seconds, it is immersed in deionized water at 15° C. for 1 minute, and then immersed in deionized water at 70° C. for 2 minutes to obtain a base membrane containing a non-woven fabric substrate and a polysulfone porous support layer;
[0125] The base film obtained as above is immersed in an aqueous solution containing m-phenylenediamine (content of 2.0wt%) and triethyl phosphate (content of 0.2wt%) for 30 seconds, and then the base film is lifted up in the vertical direction and pulled out of the aqueous solution tank, and then the excess aqueous solution on the surface is removed by using a rubber squeeze roller; then, an n-decane oil solution containing trimesoyl chloride (content of 0.11wt%) is evenly coated on the surface of the base film, and after standing for reaction for 30 seconds, the excess oil solution on the surface is removed to obtain a primary reverse osmosis membrane including a non-woven fabric substrate, a porous support layer and a polyamide desalination layer;
[0126] S2, immersing the primary reverse osmosis membrane obtained as above in a post-crosslinking aqueous solution containing 0.05 wt% m-phenylenediamine and 5 wt% ethylene glycol at 80° C. for 1 minute, and then washing in hot water at 80° C. for 1 minute;
[0127] S3, then immersed in an aqueous solution containing 0.05 wt% of AAEM / NVP copolymer at 80°C for 1 minute, and then washed in hot water at 80°C for 1 minute;
[0128] S4, then immersed in a sodium nitrite aqueous solution with a pH of 3.0 and a solute content of 0.3wt% (pH adjusted with hydrochloric acid) for 1 minute, then immersed in an aqueous solution at 60°C with a sodium sulfite content of 1wt% and an AAEM / NVP copolymer content of 0.05wt% for 1 minute, and finally washed in hot water at 90°C for 2 minutes to obtain the final reverse osmosis membrane.
[0129] The value of the ratio of the molar amount of AAEM to the total molar amount of monomers in the AAEM / NVP copolymer, x / (x+y), is 0.02, and the weight average molecular weight of the AAEM / NVP copolymer is 100,000.
[0130] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0131] Comparative Example 3
[0132] The preparation steps of the reverse osmosis membrane refer to Comparative Example 2, except that the content of ethylene glycol in the post-crosslinking aqueous solution described in step S2 is replaced from 5wt% to 10wt%; the remaining steps are the same as Comparative Example 2.
[0133] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling properties. The test results are recorded in Tables 2 and 3, respectively.
[0134] Comparative Example 4
[0135] The preparation steps of the reverse osmosis membrane refer to Example 1, except that: the value of the ratio of the molar amount of AAEM to the total molar amount of monomers in the AAEM / NVP copolymer described in steps S3 and S4 is replaced by 0.5, and the weight average molecular weight of the AAEM / NVP copolymer remains unchanged at 100,000; the remaining steps are the same as in Example 1.
[0136] The contact angle, Zeta potential, flux, desalination rate, TOC removal rate, anti-fouling properties and other properties of the prepared reverse osmosis membrane were characterized and tested, and the test results are recorded in Tables 2 and 3, respectively.
[0137] Example 1
[0138] The reverse osmosis membrane is prepared using a pilot production line, and the steps are as follows:
[0139] S1. At 25° C., a dimethylformamide solution containing 16.5 wt% polysulfone is uniformly coated on a polyester non-woven fabric substrate, the thickness of the wet coating is 150 μm, and after staying in the air for 1.5 seconds, it is immersed in deionized water at 15° C. for 1 minute, and then immersed in deionized water at 70° C. for 2 minutes to obtain a base membrane containing a non-woven fabric substrate and a polysulfone porous support layer;
[0140] The base film obtained as above is immersed in an aqueous solution containing m-phenylenediamine (content of 2.0wt%) and triethyl phosphate (content of 0.2wt%) for 30 seconds, and then the base film is lifted up in the vertical direction and pulled out of the aqueous solution tank, and then the excess aqueous solution on the surface is removed by using a rubber squeeze roller; then, an n-decane oil solution containing trimesoyl chloride (content of 0.11wt%) is evenly coated on the surface of the base film, and after standing for reaction for 30 seconds, the excess oil solution on the surface is removed to obtain a primary reverse osmosis membrane including a non-woven fabric substrate, a porous support layer and a polyamide desalination layer;
[0141] S2, immersing the primary reverse osmosis membrane obtained as above in a post-crosslinking aqueous solution containing 0.05 wt% m-phenylenediamine and 10 wt% ethylene glycol at 80° C. for 1 minute, and then washing in hot water at 80° C. for 1 minute;
[0142] S3, then immersed in an aqueous solution containing 0.05 wt% of AAEM / NVP copolymer at 80°C for 1 minute, and then washed in hot water at 80°C for 1 minute;
[0143] S4, then immersed in a sodium nitrite aqueous solution with a pH of 3.0 and a solute content of 0.3wt% (pH adjusted with hydrochloric acid) for 1 minute, then immersed in an aqueous solution at 60°C with a sodium sulfite content of 1wt% and an AAEM / NVP copolymer content of 0.05wt% for 1 minute, and finally washed in hot water at 90°C for 2 minutes to obtain the final reverse osmosis membrane.
[0144] The value of the ratio of the molar amount of AAEM to the total molar amount of monomers in the AAEM / NVP copolymer, x / (x+y), is 0.05, and the weight average molecular weight of the AAEM / NVP copolymer is 100,000.
[0145] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0146] Example 2
[0147] A reverse osmosis membrane was prepared using a pilot production line. The operating steps were similar to those of Example 1, except that the value of the molar ratio x / (x+y) of the AAEM molar amount in the AAEM / NVP copolymer to the total molar ratio of the monomers in step S3 and step S4 was replaced from 0.05 to 0.15; the remaining steps were the same as those of Example 1.
[0148] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0149] Example 3
[0150] A reverse osmosis membrane was prepared using a pilot production line. The operating steps were similar to those of Example 1, except that the value of the molar ratio x / (x+y) of the AAEM molar amount in the AAEM / NVP copolymer to the total molar ratio of the monomers in step S3 and step S4 was replaced from 0.05 to 0.30; the remaining steps were the same as those in Example 1.
[0151] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0152] Example 4
[0153] A reverse osmosis membrane was prepared using a pilot production line. The operating steps were similar to those of Example 1, except that the value of the molar ratio x / (x+y) of the AAEM molar amount to the total molar ratio of the monomers in the AAEM / NVP copolymer in steps S3 and S4 was replaced from 0.05 to 0.15, and the weight-average molecular weight of the AAEM / NVP copolymer was replaced from 100,000 to 200,000; the remaining steps were the same as those of Example 1.
[0154] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance, and the results are recorded in Tables 2 and 3, respectively.
[0155] Example 5
[0156] A reverse osmosis membrane was prepared using a pilot production line. The operating steps were similar to those of Example 1, except that the value of the molar ratio x / (x+y) of the AAEM molar amount to the total molar ratio of the monomers in the AAEM / NVP copolymer in steps S3 and S4 was replaced from 0.05 to 0.15, and the weight-average molecular weight of the AAEM / NVP copolymer was replaced from 100,000 to 300,000; the remaining steps were the same as those of Example 1.
[0157] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0158] Example 6
[0159] A reverse osmosis membrane was prepared by a pilot production line. The operating steps were similar to those of Example 1, except that the value of the molar ratio x / (x+y) of the AAEM molar amount in the AAEM / NVP copolymer to the total molar ratio of the monomers in step S3 and step S4 was replaced from 0.05 to 0.15, and the weight-average molecular weight of the AAEM / NVP copolymer was replaced from 100,000 to 500,000; the remaining steps were the same as those of Example 1.
[0160] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0161] Example 7
[0162] A reverse osmosis membrane was prepared by a pilot production line, and the operation steps were referred to Example 1, except that: the value of the molar ratio x / (x+y) of the AAEM molar amount to the total molar ratio of the monomers in the AAEM / NVP copolymer in step S3 and step S4 was replaced from 0.05 to 0.15, and the weight average molecular weight of the AAEM / NVP copolymer was replaced from 100,000 to 300,000; and,
[0163] The content of AAEM / NVP copolymer in the aqueous solution containing AAEM / NVP copolymer in step S3 is replaced from 0.05wt% to 0.01wt%, and the content of AAEM / NVP copolymer in the aqueous solution containing sodium sulfite and AAEM / NVP copolymer in step S4 is replaced from 0.05wt% to 0.01wt%;
[0164] The remaining steps are the same as those in Example 1.
[0165] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0166] Example 8
[0167] A reverse osmosis membrane was prepared by a pilot production line, and the operation steps were referred to Example 1, except that: the value of the molar ratio x / (x+y) of the AAEM molar amount to the total molar ratio of the monomers in the AAEM / NVP copolymer in step S3 and step S4 was replaced from 0.05 to 0.15, and the weight average molecular weight of the AAEM / NVP copolymer was replaced from 100,000 to 300,000; and,
[0168] The content of AAEM / NVP copolymer in the aqueous solution containing AAEM / NVP copolymer in step S3 is replaced from 0.05wt% to 0.10wt%, and the content of AAEM / NVP copolymer in the aqueous solution containing sodium sulfite and AAEM / NVP copolymer in step S4 is replaced from 0.05wt% to 0.10wt%;
[0169] The remaining steps are the same as those in Example 1.
[0170] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0171] Example 9
[0172] The reverse osmosis membrane was prepared by a pilot production line, and the operation steps were similar to those of Example 1, except that the percentage of m-phenylenediamine contained in the post-crosslinking aqueous solution in step S2 was replaced from 0.05wt% to 0.01wt%, and,
[0173] The molar ratio x / (x+y) of the molar amount of AAEM to the total monomers in the AAEM / NVP copolymer in step S3 and step S4 is replaced from 0.05 to 0.15, and the weight average molecular weight of the AAEM / NVP copolymer is replaced from 100,000 to 500,000;
[0174] The remaining steps are the same as those in Example 1.
[0175] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0176] Example 10
[0177] A reverse osmosis membrane was prepared using a pilot production line, and the operating steps were similar to those of Example 1, except that the content of m-phenylenediamine in the post-crosslinking aqueous solution in step S2 was changed from 0.05 wt % to 0.10 wt %, and
[0178] The value of the molar ratio of AAEM to the total molar ratio of monomers in the AAEM / NVP copolymer described in step S3 and step S4 is changed from 0.05 to 0.15, and the weight average molecular weight of the AAEM / NVP copolymer is changed from 100,000 to 500,000;
[0179] The remaining steps are the same as those in Example 1.
[0180] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0181] Embodiment 11
[0182] The reverse osmosis membrane was prepared by using a pilot production line. The operating steps were similar to those of Example 10, except that the ethylene glycol in the post-crosslinking aqueous solution in step S2 was replaced by methanol; the remaining steps remained unchanged.
[0183] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0184] Example 12
[0185] The reverse osmosis membrane was prepared by using a pilot production line. The operating steps were similar to those of Example 10, except that the ethylene glycol in the post-crosslinking aqueous solution in step S2 was replaced by ethanol; the remaining steps remained unchanged.
[0186] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0187] Embodiment 13
[0188] The reverse osmosis membrane was prepared by a pilot production line, and the operating steps were referred to Example 10, except that the ethylene glycol in the post-crosslinking aqueous solution in step S2 was replaced by isopropanol; the remaining steps remained unchanged.
[0189] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0190] Embodiment 14
[0191] The reverse osmosis membrane was prepared by using a pilot production line. The operating steps were similar to those of Example 10, except that the ethylene glycol in the post-crosslinking aqueous solution in step S2 was replaced by propylene glycol; the remaining steps remained unchanged.
[0192] The prepared reverse osmosis membrane was characterized and tested for performance such as contact angle, Zeta potential, flux, desalination rate, TOC removal rate, and anti-fouling performance. The test results are recorded in Tables 2 and 3, respectively.
[0193] Table 2 Partial process conditions and test results of various embodiments and comparative examples
[0194]
[0195]
[0196] Table 3 Test results of the films obtained in various embodiments and comparative examples
[0197]
[0198]
[0199] From the overall comparison between Comparative Examples 1 to 4 and Examples 1 to 14, it can be seen that when the molar ratio x / (x+y) of AAEM in the AAEM / NVP copolymer is less than 0.05 or greater than 0.3, it is difficult for it to react with the amino group in the polyamide desalination layer or the diazonium salt converted from the amino group to form a chemical bond, and the obtained reverse osmosis membrane has no obvious improvement in anti-fouling performance and isopropanol retention rate and other properties.
[0200] It can be seen from Comparative Example 4 and Examples 1 to 3 that when the molar ratio x / (x+y) of AAEM in the AAEM / NVP copolymer is between 0.05 and 0.30, the AAEM / NVP copolymer is grafted onto the cross-linked aromatic polyamide through chemical bonds. The isopropanol removal rate and anti-pollution performance can be significantly improved while keeping the flux and desalination rate almost unchanged, and the improvement effect increases with the increase of the value of x / (x+y) in the AAEM / NVP copolymer.
[0201] When the molar ratio x / (x+y) of AAEM in the AAEM / NVP copolymer is between 0.05 and 0.30, and as the weight average molecular weight of the AAEM / NVP copolymer increases, the TOC removal rate and anti-fouling performance of the reverse osmosis membrane increase, and the desalination rate also increases slightly.
[0202] When the molar ratio x / (x+y) of AAEM in the AAEM / NVP copolymer is between 0.05 and 0.30, and the concentration of the AAEM / NVP copolymer reacted with the cross-linked aromatic polyamide is increased, the TOC removal rate and anti-fouling performance of the reverse osmosis membrane can be further improved.
[0203] By reducing the concentration of m-phenylenediamine in the post-crosslinking aqueous solution, the isopropanol removal rate and anti-fouling performance decreased slightly, but were still significantly higher than the reverse osmosis membrane prepared when the molar ratio x / (x+y) of AAEM in the AAEM / NVP copolymer was less than 0.05 or greater than 0.3.
[0204] It can be seen from Examples 10 to 13 that methanol, ethanol, isopropanol and ethylene glycol all have relatively low surface tension, which can promote the diffusion of m-phenylenediamine into the cross-linked aromatic polyamide, and help accelerate the reaction with the residual acyl chloride of the cross-linked aromatic polyamide. The organic matter removal rate and anti-pollution performance of the obtained reverse osmosis membrane are comparable.
[0205] It can be seen from Example 14 and Examples 10 to 13 that, compared with methanol, ethanol, isopropanol and ethanol, propylene glycol has a higher surface tension and a weaker diffusion effect on m-phenylenediamine into the cross-linked aromatic polyamide, so the organic matter removal rate and anti-pollution performance of the obtained reverse osmosis membrane are also relatively weak.
[0206] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.
Claims
1. A polyamide reverse osmosis membrane with high organic matter rejection rate and anti-pollution, comprising: A base layer, a porous support layer and a functional separation layer; characterized in that the functional separation layer comprises: cross-linked polyamide and AAEM / NVP copolymer, and the cross-linked polyamide and the AAEM / NVP copolymer in the functional separation layer are connected by chemical bonds.
2. The polyamide reverse osmosis membrane according to claim 1, characterized in that In the functional separation layer, the AAEM / NVP copolymer is connected via a chemical bond formed between the acetoacetyl group of its side chain and the terminal amino group of the cross-linked polyamide and / or is connected via a chemical bond formed between the terminal amino group and the diazonium salt obtained after diazotization.
3. The polyamide reverse osmosis membrane according to claim 1 or 2, characterized in that: The AAEM / NVP copolymer is a product obtained by free radical polymerization of acetoacetoxyethyl methacrylate and N-vinyl pyrrolidone as monomers; Preferably, the side chain of the AAEM / NVP copolymer contains a reactive acetoacetyl group and a hydrophilic pyrrolidone group, and its chemical structure is shown in formula (I): Wherein, x and y are positive integers, and the value range satisfying the relationship x / (x+y) is 0.05 to 0.3; Preferably, the weight average molecular weight of the AAEM / NVP copolymer is greater than or equal to 5,000 and less than or equal to 1,000,000, preferably greater than or equal to 10,000 and less than or equal to 800,000, and more preferably greater than or equal to 50,000 and less than or equal to 500,000.
4. The polyamide reverse osmosis membrane according to any one of claims 1 to 3, characterized in that The cross-linked polyamide is obtained by interfacial polycondensation reaction of an aqueous solution containing m-phenylenediamine and triethyl phosphate and an oil solution containing trimesoyl chloride on the surface of the porous support layer.
5. The polyamide reverse osmosis membrane according to any one of claims 1 to 4, characterized in that The base layer is selected from one or more of polyester nonwoven fabric, polyethylene porous film and polypropylene porous film; and / or The porous support layer is selected from one or more of a polysulfone porous support layer, a polyethersulfone porous support layer and a polyacrylonitrile porous support layer.
6. The polyamide reverse osmosis membrane according to any one of claims 1 to 5, characterized in that The static contact angle of the functional separation layer in the polyamide reverse osmosis membrane is greater than or equal to 20° and less than or equal to 40°; and / or At pH=6.5, the surface Zeta potential value of the functional separation layer is -35 mV to -10 mV.
7. The polyamide reverse osmosis membrane according to any one of claims 1 to 6, characterized in that The polyamide reverse osmosis membrane has a desalination rate (Rs) of 99.6% or more, a TOC removal rate (Rt) of 85% or more, and a permeation flux of 60L / (m 2 h) and above.
8. The polyamide reverse osmosis membrane according to any one of claims 1 to 7, characterized in that The flux reduction rate of the polyamide reverse osmosis membrane after contamination is greater than or equal to 5% and less than or equal to 25%; the flux recovery rate after cleaning is greater than or equal to 98% and less than or equal to 100%.
9. The method for preparing a polyamide reverse osmosis membrane according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, subjecting an aqueous solution containing m-phenylenediamine and triethyl phosphate to an interfacial polycondensation reaction with an oil solution containing trimesoyl chloride on the surface of a porous support layer to form a cross-linked aromatic polyamide-I, thereby obtaining a primary reverse osmosis membrane; S2, contacting the primary reverse osmosis membrane obtained in step S1 with the post-crosslinking aqueous solution to react, and then washing in hot water to form a cross-linked aromatic polyamide-II, thereby obtaining a secondary reverse osmosis membrane; Preferably, the post-crosslinking aqueous solution contains m-phenylenediamine and alcohol additives; Preferably, the alcohol additive is selected from any one of methanol, ethanol, isopropanol, ethylene glycol, and glycerol; S3, contacting the secondary reverse osmosis membrane obtained in step S2 with an aqueous solution containing AAEM / NVP copolymer to react, and then washing in hot water to form a cross-linked aromatic polyamide-III, thereby obtaining a tertiary reverse osmosis membrane; S4, the three-stage reverse osmosis membrane obtained in step S3 is first immersed in a nitrous acid aqueous solution for reaction, then immersed in an aqueous solution containing sodium sulfite and AAEM / NVP copolymer for reaction, and then washed with hot water to obtain the polyamide reverse osmosis membrane.
10. Use of the polyamide reverse osmosis membrane according to any one of claims 1 to 8 or the polyamide reverse osmosis membrane prepared by the preparation method according to claim 9 in the field of desalination; Preferably, the polyamide reverse osmosis membrane is used in the fields of household water purification, industrial pure water production, industrial wastewater treatment, and removal of organic matter from pure water for the semiconductor industry.
Citation Information
Patent Citations
Modified polyamide membrane
CN101605592A
Method for strengthening contamination resistance of reverse osmosis membrane
CN102363113A
Anti-pollution reverse osmosis membrane and preparation method thereof
CN102921315A
Composite semipermeable membrane
CN105008031A
Composite semipermeable membrane and method for manufacturing same
CN105611994A
